2019
DOI: 10.3857/roj.2019.00514
|View full text |Cite
|
Sign up to set email alerts
|

Local ablative radiotherapy for oligometastatic non-small cell lung cancer

Abstract: In metastatic non-small cell lung cancer (NSCLC), the role of radiotherapy (RT) has been limited to palliation to alleviate the symptoms. However, with the development of advanced RT techniques, recent advances in immuno-oncology therapy targeting programmed death 1 (PD-1) and programmed death ligand 1 (PD-L1) and targeted agents for epidermal growth factor receptor (EGFR) mutation or anaplastic lymphoma kinase (ALK) translocation allowed new roles of RT in these patients. Within this metastatic population, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
(58 reference statements)
2
9
0
Order By: Relevance
“…as a transitional state between the localized and polymetastatic states, oligometastasis is the state most favorable for local therapy to impact long‐term survival 5 . Recovery rates from oligometastasis have been confirmed in locally treated cases of colorectal cancer as well as in non‐SCLC patients 6,7 . However, since ED‐SCLC is a systemic disease, oligometastatic cases are rare.…”
Section: Introductionmentioning
confidence: 97%
“…as a transitional state between the localized and polymetastatic states, oligometastasis is the state most favorable for local therapy to impact long‐term survival 5 . Recovery rates from oligometastasis have been confirmed in locally treated cases of colorectal cancer as well as in non‐SCLC patients 6,7 . However, since ED‐SCLC is a systemic disease, oligometastatic cases are rare.…”
Section: Introductionmentioning
confidence: 97%
“…For patients with advanced NSCLC and no targetable gene alterations, platinum-based doublet chemotherapy remains the standard first-line treatment [ 1 , 2 , 7 ]. Despite the recent progress in the management of advanced NSCLC, the prognosis of these patients remains poor, and the reported median overall survival is only 8–12 months [ 1 , 7 , 14 ]. By contrast, in patients with targetable gene alterations [ 15 , 16 , 17 , 18 , 19 ], targeted therapies have improved the median overall survival to 26–46 month.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, attempts are currently being made to impose ablative (stereotactic body radiation therapy, SBRT) or moderate hypofractionated RT (HRT) protocols both in early stages without surgical resolution and in advanced stages (Iyengar et al 2018). The efficacy of these regimens has been shown through phase II clinical trials, which demonstrated better progression-free survival and overall patient survival (Suh & Cho 2019, Folkert & Timmerman 2017, Cuccia et al 2020. Although still under debate, few innovations in RT have had the impact of these modalities, which achieved 85-90% local control (Choi 2019, Murray et al 2017, Weder et al 2018.…”
Section: Introductionmentioning
confidence: 99%